SOSIALISASI DAN PELATIHAN BAHASA JEPANG BAGI SISWA SEBAGAI UPAYA PENGEMBANGAN POTENSI NAGARI DI LENGAYANG KABUPATEN PESISIR SELATAN - Nabila Intani Umari; Ferdinal Ferdinal (BULETIN ILMIAH NAGARI MEMBANGUN, 2023)
The enhancement of foreign language skills, such as English, is notably essential in Indonesia, particularly in improving tourism services. Nagari Kambang Barat is an area abundant in economic potential, including trade, agriculture, fishing, and various tourism-related occupations. The aim of this endeavor is to foster students' interest in learning and mastering the Japanese language, thereby enhancing the human resources' quality within the Nagari Kambang Barat Lengayang area for the development of its tourism sector. These activities are conducted in Nagari Kambang Barat, Lengayang, Pesisir Selatan Regency, West Sumatra. The approach involves, firstly, socialization to underscore the significance of mastering foreign languages like Japanese in tourism development. Secondly, Japanese language training aimed at introducing fundamental knowledge of the language. Socialization was provided to 39 students of SMPN 1 Lengayang, Pesisir Selatan Regency, West Sumatra. The outcomes of these socialization and Japanese language training activities indicate the participants' realization of the importance of foreign language proficiency, especially in Japanese, to explore tourism potential. Subsequently, ongoing training and guidance by universities, governmental bodies, or relevant stakeholders are crucial to augment both the quality and quantity of the populace. In the future, participants hope for comprehensive and continuous learning opportunities in foreign languages, specifically Japanese.